2003
DOI: 10.1097/00004694-200309000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aprotinin in Reducing Blood Loss in Spinal Fusion for Idiopathic Scoliosis

Abstract: Aprotinin is a proteinase inhibitor with antifibrinolytic properties that has found widespread application during cardiac surgical procedures due to its ability to decrease blood loss and transfusion requirements. Recently it has been used by orthopedic surgeons in hip replacement and other major surgeries except for scoliosis surgery, which is known to be associated with major blood loss. To evaluate the effect of aprotinin in reducing blood loss during spinal fusion surgery for idiopathic scoliosis, a double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…Aprotinin (Trasylol Ò , Bayer), an antifibrinolytic, has proven to be very effective in reducing preoperative blood loss in major orthopaedic procedures, thereby minimizing the need for blood products [5,8,14]. Although its exact mechanism of action has not been completely understood, it modulates coagulation factors by inhibiting plasmin and kallikrein activity [11,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aprotinin (Trasylol Ò , Bayer), an antifibrinolytic, has proven to be very effective in reducing preoperative blood loss in major orthopaedic procedures, thereby minimizing the need for blood products [5,8,14]. Although its exact mechanism of action has not been completely understood, it modulates coagulation factors by inhibiting plasmin and kallikrein activity [11,15].…”
Section: Introductionmentioning
confidence: 99%
“…Aprotinin has been extensively used in cardiothoracic surgery [2,13] and recently in orthopaedic surgery [4,5,8,12,14]. However, despite the expanding role of aprotinin in orthopaedic surgical cases, there is limited data evaluating the role of this antifibrinolytic in scoliosis surgery in children with neuromuscular disease.…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Of all the types of surgeries, spinal fusion and cardiac operations have been the most extensively studied (Tables II and III). For patients with idiopathic scoliosis, predonation with or without the addition of erythropoietin is probably the safest and the most effective way to avoid the use of allogenic blood products.…”
mentioning
confidence: 99%
“…However, one randomized prospective study did not show any reduction in blood loss in adolescents undergoing surgery for idiopathic scoliosis 37 . Another study demonstrated a reduction in intraoperative and postoperative blood loss, but not in allogeneic blood transfusion, in patients treated with posterior spine fusion 38 .…”
Section: Aprotininmentioning
confidence: 95%